Biological nitrification inhibition (BNI)—A novel strategy to regulate nitrification in agricultural systems - Subbaraoa, Guntur V.; Sahrawat, Kanwar Lal; Nakahara, K.; Ishikawa, T.; Kudo, N.; Kishii, M.; Rao, Idupulapati M.; Hash, C.T.; George, T.S.; Rao, P.S.; Nardi, P.; Bonnett, D.; et al. (Elsevier, 2012)
Human activity has had the single largest influence on the global nitrogen (N) cycle by introducing unprecedented amounts of reactive-N into ecosystems. A major portion of this reactive-N, applied as fertilizer to crops, leaks into the environment with cascading negative effects on ecosystem functions and contributes to global warming. Natural ecosystems use multiple pathways of the N-cycle to regulate the flow of this element. By contrast, the large amounts of N currently applied in agricultural systems cycle primarily through the nitrification process, a single inefficient route that allows much of the reactive-N to leak into the environment. The fact that present agricultural systems do not channel this reactive-N through alternate pathways is largely due to uncontrolled soil nitrifier activity, creating a rapid nitrifying soil environment. Regulating nitrification is therefore central to any strategy for improving nitrogen-use efficiency. Biological nitrification inhibition (BNI) is an active plant-mediated natural function, where nitrification inhibitors released from plant roots suppress soil-nitrifying activity, thereby forcing N into other pathways. This review illustrates the presence of detection methods for variation in physiological regulation of BNI-function in field crops and pasture grasses and analyzes the potential for its genetic manipulation. We present a conceptual framework utilizing a BNI-platform that integrates diverse crop science disciplines with ecological principles. Sustainable agriculture will require development of production systems that include new crop cultivars capable of controlling nitrification (i.e., high BNI-capacity) and improved agronomic practices to minimize leakage of reactive-N during the N-cycle, a critical requirement for increasing food production while avoiding environmental damage.